Understanding mathematical word problem-solving skills among elementary schoolers through meta-analyses - Vessonen, Terhi (LUMAT-B: International Journal on Math, Science and Technology Education, 2025)
Since enabling the application of mathematical skills in various situations, mathematical word problem-solving skills are an important set of skills in modern society. These skills are especially important in the first years of formal schooling since the foundation for later learning is laid then. Like other mathematical skills, word problem-solving skills are likely shaped by multiple, interrelated skills such as language skills, motivation, characteristics of the task, and the received instruction. The overall aim of this thesis was to investigate individual, task, and educational interventions’ characteristics associated with elementary schoolers’ mathematical word problem-solving skills. Through three meta-analytic studies, I investigated how individual characteristics such as reading comprehension, number naming, and motivation relate to performance; how task characteristics like irrelevant information and number of steps required; and how word problem-solving intervention features relate impact students’ word problem-solving skills. In this lectio praecursoria, I reflect on the importance of understanding these interrelated factors to better support diverse learners and to design educational interventions that are both effective and sustainable.